A pilot study investigating whether quantitative sensory testing alters after treatment in patients with fibromyalgia. Issue 4 (November 2018) - Wodehouse, Theresa; Poply, Kavita; Ramaswamy, Shankar; Snidvongs, Saowarat; Bourke, Julius; Tahir, Hasan; Ullrich, Kristin; Mehta, Vivek
Background: Fibromyalgia is a chronic musculoskeletal pain condition that is often associated with sleep disturbances and fatigue. The pathophysiology of fibromyalgia is not understood, but indirect evidence suggests a central dysfunction of the nociceptive modulating system. The aim of this study was to evaluate whether quantitative sensory testing detects a change in pain thresholds in fibromyalgia patient receiving pregabalin treatment. Methods: A total of 25 patients were recruited for the study and received routine pregabalin, but only 14 patients completed the treatment. Assessment of pressure pain thresholds and changes in conditioned pain modulation using ischaemic pain as a conditioning stimulus were measured at baseline and every 4 weeks for 12 weeks. Fibromyalgia impact questionnaire, PainDETECT and SF-12 were also completed. Results: Patients with fibromyalgia demonstrated a less-efficient conditioned pain modulation at baseline. An efficient conditioned pain modulation was observed at 1 month and this was maintained until the final visit. Pressure pain thresholds (PPTs) showed a significant improvement from baseline. Patients also reported a similar magnitude of improvements in PainDETECT, fibromyalgia impact questionnaire (FIQ) and its impact on daily life and change in outcome for SF-12. Conclusion: This pilot study reports an increase in PPTs and improved conditioned pain modulation response after commencing pregabalin, which was maintained at 12 weeks, and this was supported by positive pain scores. Pregabalin is a licenced treatment for fibromyalgia in Europe, and its response to central sensitisation, particularly 'dynamic responses', has not been reported. We conclude that pregabalin has the potential to reduce peripheral and central sensitisation in patients with fibromyalgia, as measured using quantitative sensory testing.